Pengaruh Profitabilitas dan Ukuran Perusahaan Terhadap Struktur Modal Pada Perusahaan Manufaktur Subsektor Farmasi di Bursa Efek Indonesia Tahun 2017-2020 - Romitha, Sintikhe (UNIB Press, 2024)
The purpose of this study was to analyze the effect of profitability (ROA), company size (Size) on the capital structure of pharmaceutical companies listed on the Indonesia Stock Exchange in 2017-2020. The sample of this research is 8 pharmaceutical companies. The analytical method used in this study is panel data regression using the Eviews 10 application. Hypothesis testing is the determinant coefficient and T test. The results of the analysis in this study simultaneously show that the profitability variable and firm size variable have a significant effect on capital structure. The results of the study partially show that profitability has a significant effect on capital structure. Firm size variable has no significant effect on capital structure. Keyword: Profitability; Capital Structure; Company Size